Potential benefits of selenium supplementation in patients with kidney disease - Shirinsadat Badri; Sahar Vahdat; Morteza Pourfarzam; Samaneh Assarzadeh; Shiva Seirafian; Sara Ataei (Wolters Kluwer Medknow Publications, 2021)
Trace element deficiency is common among patients with end-stage renal disease (ESRD); the reason is that since these patients undergo dialysis, they lose these elements more than healthy people, and also the use of trace elements is restricted due to loss of appetite. Selenium (Se) is a trace element that is essential for the oxidative stress defense system. Se deficiency leads to some complications similar to those often seen in ESRD patients, such as all-cause mortality due to cardiovascular diseases, bone loss, uric acid elevation, and anemia. This article aims to review the evidence on consequences of Se deficiency in ESRD patients, as well as effects of Se supplementation in hemodialysis patients. Multiple databases were searched to summarize the available evidence on selenium's role in kidney diseases. Since the complications of ESRD and those of Se deficiency are mostly similar, this triggers the idea that Se deficiency may be considered as a cause of these problems, but it needs to be more assessed that Se deficiency is a single factor or there are other factors participated in. Also the role of Se supplementation on resolving the mentioned complications, needs to be more studied through well-designed clinical studies.